Evidence of the involvement of the polymorphisms near MSX1 gene in non-syndromic cleft lip with or without cleft palate. Issue 7 (July 2015) - Gurramkonda, Venkatesh Babu; Hussain Syed, Altaf; Murthy, Jyotsna; Lakkakula, Bhaskar V.K.S.
Abstract Objective Non-syndromic cleft lip, with or without cleft palate (NSCL/P) is a common craniofacial birth defect, characterised by an incomplete separation between nasal and oral cavities without any other congenital anomaly in humans. Several genes which play a role in cell differentiation, migration, growth and apoptosis, have been associated with clefting. The purpose of this study was to investigate the association between single-nucleotide polymorphisms (SNPs) near MSX1 gene and NSCL/P among South Indian population. Methods A case-control analysis of five single nucleotide polymorphisms near MSX1 gene (rs11726039, rs868257, rs6446693, rs1907998 and rs6832405) was carried out in 173 patients with NSCL/P and 176 unaffected controls to determine their association with NSCL/P. Results All SNPs were polymorphic in the study population. Comparisons of allele and genotype frequencies revealed that the C variant allele and the TC/CC genotypes of rs11726039 was significantly higher in controls than in the NSCL/P group (OR: 0.63; 95% CI: 0.41 − 0.097; p = 0.037). However, neither of these findings remained significant after Bonferroni correction for multiple comparisons. The frequencies of rs868257, rs6446693, rs1907998 and rs6832405 minor alleles and genotypes were similar between the control and NSCL/P groups. No significant linkage disequilibrium (LD) was observed. Genotype-genotype interaction and the haplotype analysis did not reveal any significant association with NSCL/P. Conclusions The study results were suggestive of a positive association between MSX1 rs11726039 and NSCL/P in the South Indian population.